A comparative analysis of the strain-line pattern in the human left ventricle: experiments vs modelling. Issue 3 (3rd July 2016) - Evangelista, A.; Gabriele, S.; Nardinocchi, P.; Piras, P.; Puddu, P.E.; Teresi, L.; Torromeo, C.; Varano, V.
Abstract : We present and discuss a method to infer noninvasively information on the fibre architecture in real human left ventricle walls. The method post-processes the echocardiographic data acquired by three-dimensional speckle tracking echocardiography through a MatLab-based protocol, already presented, discussed and validated. Our results indicate the difference between the role of endocardial and epicardial principal strain lines, at the systolic peak, and set the bases for possible future investigations aimed to analyse the onset of specific cardiac diseases through noninvasive analysis of LV fibre architecture. Moreover, we set a rational statistical analysis to investigate the reliability of the proposed method.